2021
DOI: 10.1186/s43066-020-00072-6
|View full text |Cite
|
Sign up to set email alerts
|

Arctigenin attenuates CCl4-induced hepatotoxicity through suppressing matrix metalloproteinase-2 and oxidative stress

Abstract: Background In spite of the huge advances in recent medicine, there is no effective drug that completely protects the liver from toxic materials. This study was conducted to investigate the hepatoprotective effect of arctigenin from burdock (Arctium lappa) against carbon tetrachloride (CCl4)-induced liver injury. Results Arctigenin pre-administration reduced hepatotoxicity markers significantly as compared to CCl4 group. In addition, both silymarin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 42 publications
3
6
0
Order By: Relevance
“…The injury also occurs in the form of central vein and hepatic sinusoidal dilatation, vascular congestion, and vacuolar degeneration as noticed by Dianzani et al (1969) and Kakar et al (2004). Such knowledge is in accordance with the Hassan et al (2012Hassan et al ( , 2013 and Eid et al (2015). Degenerative alterations in liver cells have also been observed by Boshra and Moustafa (2013), Mourad and Khadrawy (2012).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The injury also occurs in the form of central vein and hepatic sinusoidal dilatation, vascular congestion, and vacuolar degeneration as noticed by Dianzani et al (1969) and Kakar et al (2004). Such knowledge is in accordance with the Hassan et al (2012Hassan et al ( , 2013 and Eid et al (2015). Degenerative alterations in liver cells have also been observed by Boshra and Moustafa (2013), Mourad and Khadrawy (2012).…”
Section: Discussionsupporting
confidence: 88%
“…This study design of repeated serum biomarker measurements for each treatment provides a good opportunity to distinguish these effects of changes in BPA concentrations on liver function. Liver function activity of enzymes such as AST and ALT level was also increased compared with control rats (Hassan et al, 2012;Korkmaz et al, 2010). Nonetheless, a recovery of the balance relative to control rats was observed after being fed with Se concomitantly with BPA (Favier, 2003;Helal et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…An increase in their concentration is a symbol of liver injury and disease [24]. Our results showed that the serum levels of AST and ALT significantly increased in response to CCl 4 and this agreed with previous studies [18,25]. This increase in the serum levels of these enzymes has been associated with liver damage since they are usually produced from hepatocytes during hepatonecrosis [26].…”
Section: Impact Of CCL 4 Administration On Oval Cell Regenerationsupporting
confidence: 92%
“…AST is localized in the mitochondria whereas ALT is distributed throughout the cytoplasm, ALT is more specific to the liver and is thus a better parameter for detecting liver injury (Lee et al,2017, Palanivel et al,2008. Lipid peroxidation caused by CCl4 causes cell membrane disruption leading to increased cell membrane permeability and AST and ALT leakage out from the liver into the bloodstream which explains the elevation of these enzymes level in blood after administration of CCl4 (Hus et al,2020, Kanawati et al,2021. The treatment of intoxicated rats with PSH in PS+CCl4 reduced ALT and AST serum activities to the normal level.…”
Section: Discussionmentioning
confidence: 99%